Food plants in pollen records from ancient Southern Arabia: The evidences from Sumhuram (Southern Oman). (June 2020) - Bellini, Cristina; Pavan, Alexia; Pignotti, Lia; Gonnelli, Tiziana; Lippi, Marta Mariotti
Abstract: Archaeological excavations of the ancient city of Sumhuram (2nd century BC- 5th century AD), a port along the frankincense trade route in Dhofar, Southern Oman, offered the chance to gain new insights into the diet of the inhabitants. In spite of the mainly sandy nature of the sediments in the site, which does not favour good preservation of plant materials, pollen analyses and sporadic findings of starch grains, seeds and fruits allowed evidence of food plants to be gathered. Pollen and starch grains of cereals at Sumhuram attested to the consumption of major crops, like wheat and barley, as well as minor crops, such as the millets. Cereal pollen from a pit in the city helped strengthen the archaeological interpretation of this structure as foodstuff storage. Both date palm pollen and stones recovered in two rooms testified to the use of this plant, largely diffused in Arabia. Even though the provenance of these foodstuffs remains dubious - they could have been locally cultivated/gathered or imported from other territories - the outcome of our Modern Analogues study in wadi estuaries enabled us to attribute varying origins to pollen sources in the past record. Highlights: Pollen was instrumental in gaining insights into food plant use in pre-Islamic Oman. Present vegetation and pollen rain studies supported interpretation of past records. Cereal pollen in a pit confirmed the archaeological hypothesis of foodstuff storage. Exploitation of the date palm is attested by both pollen and charred stones. Declining woody plant pollen reflects shrubland clearing rather than aridification.